Did the COVID-19 Lock-Down Make Us Better at Working in Virtual Teams? - Klonek, Florian; Kanse, L.; Wee, S.; Runneboom, Cecilia; Parker, Sharon (SAGE PUBLICATIONS INC, 2022)
The COVID-19 pandemic was a key event forcing an increase in virtual work. Drawing on event system theory, we examined whether virtual teams showed enhanced processes in later stages of the pandemic compared to the early stages of the pandemic. We collected data from 54 virtual teams (N = 152 individuals) who worked on a 30-minute task. We measured team processes and performance. Virtual teams during the post-transition phase (June–August 2020) showed better levels of team action processes and conflict management compared to teams working in the immediate transition phase (March–May 2020), indicative of an adaptation effect.